2006
DOI: 10.1016/j.dnarep.2005.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Msh2 and Msh6 subunits to the asymmetric ATPase and DNA mismatch binding activities of Saccharomyces cerevisiae Msh2–Msh6 mismatch repair protein

Abstract: Previous analyses of both Thermus aquaticus MutS homodimer and Saccharomyces cerevisiae Msh2-Msh6 heterodimer have revealed that the subunits in these protein complexes bind and hydrolyze ATP asymmetrically, emulating their asymmetric DNA binding properties. In the MutS homodimer, one subunit (S 1 ) binds ATP with high affinity and hydrolyzes it rapidly, while the other subunit (S 2 ) binds ATP with lower affinity and hydrolyzes it at an apparently slower rate. Interaction of MutS with mismatched DNA results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 37 publications
(83 reference statements)
3
43
0
Order By: Relevance
“…Once Msh2-Msh6 is bound to base-paired DNA, ATP binding causes Msh2-Msh6 to directly dissociate from DNA (21). In contrast, when Msh2-Msh6 is bound to a mispair, ATP hydrolysis at the Msh6 site is inhibited, which then favors binding of ATP at the Msh2 site (32,37,38). A similar dual ATPbound state can be achieved with ATP␥S (21,32).…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 72%
“…Once Msh2-Msh6 is bound to base-paired DNA, ATP binding causes Msh2-Msh6 to directly dissociate from DNA (21). In contrast, when Msh2-Msh6 is bound to a mispair, ATP hydrolysis at the Msh6 site is inhibited, which then favors binding of ATP at the Msh2 site (32,37,38). A similar dual ATPbound state can be achieved with ATP␥S (21,32).…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 72%
“…In the msh6 strain, levels of both contractions and sectored colonies dramatically dropped, and were not statistically different from those In order to determine if MSH2 ATPase activity was required for heteroduplex formation, we introduced a point mutation in the MSH2 Walker B motif (Glu768->Ala768). This mutation does not affect heterodimerization nor the ability to bind mismatched DNA but dramatically reduces ATPase activity and results in mutation rates similar to the null allele [52,53]. The msh2-E768A gene was placed under the control of the same doxycyclin-regulated (TetO) 7 promoter and expressed as previously.…”
Section: Muts Complexes Promote Cag/ctg Heteroduplex Formation or Stamentioning
confidence: 99%
“…Recent studies have revealed asymmetry in the ATPase activity of the two subunits in the MutS dimer, 14,15,[18][19][20][21][22] which correlates with asymmetry in their DNA-binding activity; only one subunit provides Phe and Glu residues for base-specific interactions with the mismatch. 7,8,23 One subunit (S1 in MutS, Msh6 in Msh2-Msh6) binds ATP with high affinity and hydrolyzes it rapidly when MutS is alone or with matched DNA, while the other subunit (S2 in MutS, Msh2 in Msh2-Msh6) appears to hydrolyze ATP slowly.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the ATPase activities of the two subunits are linked, but exactly how ATP binding, hydrolysis, and product release are coordinated between the two is still under investigation. 18,20 The subunit asymmetry potentially increases the complexity of coupling between the DNA-binding and ATPase activities of MutS, as there are now up to nine possible nucleotide-bound and nucleotide-free forms of the dimer whose formation and decay could influence its actions on DNA during mismatch repair.…”
Section: Introductionmentioning
confidence: 99%